Corporate Governance and a Paradigm Strategy by Multinational Enterprises in Emerging Markets - Anyachebelu, Obianuju; Asortse, Sefa; Igwe, Anthony Aniagbaoso (International Journal Of Management And Economics Invention, 2021)
This qualitative investigation meticulously identified challenges to corporate governance in operations of Multinational Enterprises (MNEs) in diverse situational positions in emerging markets. These challenges are weak macro institutions, strict government interest and influence, over formalized institutional structure, and overbearing political influence and the obvious; information asymmetries. A flexible mixed allegiance paradigm strategy was identified. It provides alignment of diversities and equilibrium based on micro operational efficacies of the multinational enterprise which are experienced and skilled workforce, related to locality of interest, management of loyalty, trust and negotiation hinged on acceptable agreements to member countries. Trust is emphasized as important for international business.